The evaluation of anxiety, depression and Type D personality in a sample of cardiac patients - F. Caccamo; I. Stefani; A. Pinton; V. Sava; R. Carlon; C. Marogna (Cogent Psychology, 2020)
Many psychological factors influence the onset and prognosis of heart disease, among the most studied, there are personality traits, depressive and anxious experiences. Type D personality, characterized by high levels of social inhibition and negative affectivity, is associated with unfavourable prognosis for cardiac patients. Depressive and anxious symptoms influence the onset of cardiac disorders, the management of the disease and their impact on quality of life. Aim of this study is to evaluate the impact of cardiac rehabilitation on social inhibition, negative affectivity, anxious and depressive symptoms in cardiac patients. Patients were recruited at the Rehabilitation Cardiology Unit of Cittadella Hospital, after an acute cardiac event, they were enrolled to attend a cardiac rehabilitation program. Patients were administered the Hospital Anxiety and Depression Scale (HADS), and the Type D Scale (DS-14). Results showed significant differences between the pre- and post-test evaluation: a decrease in the Negative Affectivity subscale (DS-14) and in the Anxiety subscale and emotional distress (HADS). Other differences resulted with respect to the sociodemographic variables, particularly unmarried patients showed higher levels of anxiety at the post-test with respect to married patients, also working patients showed lower levels of depression than those who were unemployed or retired because having a job helps patients to feel less depressed because they can concentrate their resources and thoughts on other things that are not just the disease. The study demonstrated that Cardiac Rehabilitation has beneficial effects on the psychological state of patients to stimulate awareness of the disease, modification of its perception and exchange of information valuable to reorganize private and professional lives.